The effects of three different exercise modalities on markers of male reproduction in healthy subjects: a randomized controlled trial - Hajizadeh Maleki, Behzad; Tartibian, Bakhtyar; Chehrazi, Mohammad (Reproduction (Cambridge, England), 2017)
The aim of this study was to investigate the effects of moderate-intensity continuous training (MICT), high-intensity continuous training (HICT) and high-intensity interval training (HIIT) on markers of male reproduction including seminal markers of oxidative stress and inflammation as well as semen quality and sperm DNA integrity in healthy human subjects. A total of 397 healthy male volunteers were screened and 280 were randomly assigned to one of the MICT (n = 70), HICT (n = 70), HIIT (n = 70) and non-exercise (NON-EX, n = 70) groups. Subjects had inflammatory markers (IL-1β, IL-6, IL-8 and TNF-α), oxidants (ROS, MDA and 8-isoprostane), antioxidants (SOD, catalase and TAC), semen parameters and sperm DNA damage measured at baseline (T1), the end of week 12 (T2), the end of week 24 (T3), and 7 (T4) and 30 days (T5) after training. Chronic MICT, HICT and HIIT attenuated seminal markers of oxidative stress and inflammation with different kinetics for the three types of exercise (P < 0.05), and these changes were correlated with favorable improvements in semen quality parameters and sperm DNA integrity (P < 0.05). MICT was superior to HICT and HIIT in the improvements of markers of male reproductive function (P < 0.05). In conclusion, different exercise modalities favorably affect markers of male reproduction with different kinetics, suggesting intensity-, duration- and type-dependent adaptations to exercise training in healthy human subjects.